2008
DOI: 10.1007/s10565-008-9104-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic investigation of urinary markers of carbon-tetrachloride-induced hepatic fibrosis in the Hanover Wistar rat

Abstract: Proteomic techniques such as two-dimensional gel electrophoresis (2-DGE) and mass spectrometry have become important tools for the identification of novel biomarkers of toxicity and disease. Ideally, such biomarkers need to be sensitive and organ specific, but, recently, it has become apparent that it would be an additional benefit to be able to measure biomarkers in samples obtained using non-invasive methods. The present study is concerned with the identification of novel urinary markers of hepatic fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Urine samples have been scarcely studied to identify liver fibrosis markers, and we were able to identify only one experimental report that analyzed urine samples with respect to hepatic fibrosis (Smyth et al 2009). In that study, LCN2 was identified as a marker of carbon tetrachloride-induced liver fibrosis (Smyth et al 2009). Our study has shown for the first time that urinary LCN2 levels (ULCR) are elevated in CHC patients with significant fibrosis compared to patients with no or minimal fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Urine samples have been scarcely studied to identify liver fibrosis markers, and we were able to identify only one experimental report that analyzed urine samples with respect to hepatic fibrosis (Smyth et al 2009). In that study, LCN2 was identified as a marker of carbon tetrachloride-induced liver fibrosis (Smyth et al 2009). Our study has shown for the first time that urinary LCN2 levels (ULCR) are elevated in CHC patients with significant fibrosis compared to patients with no or minimal fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…In 2003, for example, it was shown that the enzymatic activity of D-DT is detectable in the epidermis of the skin and is increased after UV irradiation [26]. Other studies employing proteomics demonstrated that D-DT is elevated in the rat liver [27] and in the urine in a model of carbon tetrachloride-induced hepatic fibrosis [28], and that its expression increased after selenite induced apoptosis in HeLa cancer cells [29]. Only in the last four years studies have appeared that focused on the biological role of D-DT [3032].…”
Section: Introductionmentioning
confidence: 99%
“…in rats the oral LD 50 of NDMA has been reported to be 40 mg/kg body weight (ATSDR, 1989). Other compounds which similarly to NDMA induce hepatic fibrosis in laboratory animals are: nitrosodiethylamine (NDEA), thioacetamide and carbon tetrachloride (George & Chandrakasan, 2000; Shimizu et al , 2001; Palacios et al , 2008; Smyth et al , 2009; Karantonis et al , 2010). The available literature suggests that NDMA-induced hepatic fibrosis in rats is a very successful and reproducible model for various clinical and toxicological studies.…”
Section: Introductionmentioning
confidence: 99%